2002
DOI: 10.1592/phco.22.8.586.33204
|View full text |Cite
|
Sign up to set email alerts
|

Etomidate for Procedural Sedation in the Emergency Department

Abstract: Although controversial, etomidate holds promise as a potent sedative agent for patients undergoing painful procedures in the emergency department. A large prospective evaluation is needed to document the performance and complications of this agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Although there are little data to describe the minimum dose of these agents required to induce adequate sedation, the doses used in this study are close to what has been described in previous studies of ED procedural sedation. [4][5][6][9][10][11] We observed some differences in the two agents used, including changes in blood pressure, time of the procedure, and procedural success. It appears that using either etomidate or propofol for the sedation of critically ill patients has rates of complications similar to previous reports for both agents in more stable patients.…”
Section: Discussionmentioning
confidence: 94%
“…Although there are little data to describe the minimum dose of these agents required to induce adequate sedation, the doses used in this study are close to what has been described in previous studies of ED procedural sedation. [4][5][6][9][10][11] We observed some differences in the two agents used, including changes in blood pressure, time of the procedure, and procedural success. It appears that using either etomidate or propofol for the sedation of critically ill patients has rates of complications similar to previous reports for both agents in more stable patients.…”
Section: Discussionmentioning
confidence: 94%
“…4,13,45,49 It has been clearly demonstrated that many of the drugs used in procedural sedation and analgesia predispose the patient to the development of hypoxemia, and that drug combinations, especially benzodiazepines and opioids, have a potentiating effect in suppressing respirations. 49,53 Despite the evidence that desaturation may occur during procedural sedation and analgesia, there is little information regarding the clinical significance of transient desaturation.…”
Section: Critical Questionsmentioning
confidence: 99%
“…A substantial body of evidence supports the routine safe use of procedural sedation and analgesia by emergency physicians. [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] …”
mentioning
confidence: 99%
“…The main disadvantage is gastric irritation, which can lead to vomiting. Also, it has no intrinsic analgesic effect [31]. Chloral hydrate produces effective sedation in 80-90% of patients [32].…”
Section: Hypnoticsmentioning
confidence: 99%